INTERPRETASI KATA LOGOS DAN THEOS DALAM YOHANES 1:1 - Yusuf L. M. (SEKOLAH TINGGI TEOLOGI INJILI SETIA SIAU, 2020)
Logos is Theos has always been a topic of heated discussion among Christian theologians. This subject is also often misinterpreted so that interpretations emerge that are not biblical or not following their original meaning. Logos is often accused of originating from the concept of Greek philosophy because John is considered to be much influenced by the Hellenistic world. Logos is often interpreted in the context of John 1:1 only divine, a God, or inferior to God because grammatically, the phrase